The Costs of Home-Based ART Initiation and Mobile Refill in Uganda. (4th October 2017) - Roberts, D Allen; Asiimwe, Stephen; Turyamureeba, Bosco; Barnabas, Ruanne
Abstract: Background: Antiretroviral therapy (ART) is effective at reducing HIV-associated morbidity, mortality, and transmission, but 20 million people who meet WHO eligibility criteria for ART are not in care. While decentralized care is a promising strategy to expand ART access, the costs of implementing a community-based model on a large scale remain unknown. Methods: The DO-ART study is a randomized trial of community- vs. clinic-centered ART delivery in South Africa and Uganda using 12-month viral suppression as the primary outcome. We evaluated the costs of home-based ART initiation and refill in southwest Uganda using time-and-motion studies, staff interviews, and budgetary analysis. Costs categories included medications, supplies, personnel, building and utilities, start-up, vehicles, and community mobilization. We used a programmatic perspective with a 3% discount rate and removed research-associated costs. Results: The largest cost categories included medications, supplies, and salaries, constituting 41%, 27%, and 17% of the total cost, respectively. Time-and-motion studies revealed that each outreach worker could serve an average of three patients per day in a fully decentralized model. In a scenario of providing home-based ART to 1400 patients aross seven sub-counties, the yearly per-patient cost was estimated to be $304 (2016 USD), which is similar to literature reports of the costs of facility-based ART provision. Conclusion: These estimates suggest that home-based ART may be a realistic delivery option, especially if it is found to be effective at improving viral suppression. Further research is needed to evaluate how this intervention can most efficiently scale to provide widespread ART access over a large geographic area. Disclosures: All authors: No reported disclosures.